we have the equation 1 and 2, we need the values of y and x with elimination method.
(1) x+3y=-14
(2) -4x-3y=2
The we have to trying to get rid of the Ys. In this case the Ys have a common factor so we dont havo to multiply for another number. So in the Ys we have 3y -3y equal to 0.
(1) x =-14
(2) -4x=2
Now, we have the value of x in the first equation. Then, we replace x on the second funtion to find the value of y:
(2) -4x-3y=2
-4(-1) - 3y=2
4 - 3y = 2, we solve for y
-3y = 2 -4
-3y= -2
y = -2/-3
y= 2/3
To confrim this we replace the x and y values